Kombinasi Teh Putih dan Bunga Telang dalam Minuman Sehat: Penelitian - Tri Wahyuni Indah Permata; Ertauli Panjaitan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Butterfly Pea White Tea has various health benefits, one of which is its high antioxidant content. The combination of both in one drink can provide great benefits. This study aims to test the taste, aroma, and color of white tea and butterfly pea flowers. This study used a quantitative descriptive design with a sample of 32 respondents who were tested for acceptance of taste, aroma, and color. The results of this study indicate that the combination of butterfly pea white tea produces a drink with a soft taste, refreshing aroma, and attractive color. Consumer surveys showed a high level of satisfaction with 85% of respondents stating that this drink has an attractive taste and improves skin health and immunity. The combination of white tea and butterfly pea flowers produces a drink that not only has a color, taste, and aroma that consumers like, but also has health benefits. This drink has the potential to become a popular health drink on the market.